Molecular fluorescence-guided surgery of peritoneal carcinomatosis of colorectal origin: a single-centre feasibility study. (December 2016) - Harlaar, Niels J; Koller, Marjory; de Jongh, Steven J; van Leeuwen, Barbara L; Hemmer, Patrick H; Kruijff, Schelto; van Ginkel, Robert J; Been, Lukas B; de Jong, Johannes S; Kats-Ugurlu, Gursah; Linssen, Matthijs D; Jorritsma-Smit, Annelies; et al.
Summary: Background: Optimum cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (HIPEC) is essential for the curative treatment of peritoneal carcinomatosis of colorectal origin. At present, surgeons depend on visual inspection and palpation for tumour detection. Improved detection of tumour tissue using molecular fluorescence-guided surgery could not only help attain a complete cytoreduction of metastatic lesions, but might also prevent overtreatment by avoiding resection of benign lesions. Methods: For this non-randomised, single-centre feasibility study, we enrolled patients with colorectal peritoneal metastases scheduled for cytoreductive surgery and HIPEC. 2 days before surgery, 4·5 mg of the near-infrared fluorescent tracer bevacizumab-IRDye800CW was administered intravenously. The primary objectives were to determine the safety and feasibility of molecular fluorescence-guided surgery using bevacizumab-IRDye800CW. Molecular fluorescence-guided surgery was deemed safe if no allergic or anaphylactic reactions were recorded and no serious adverse events were attributed to bevacizumab-IRDye800CW. The technique was deemed feasible if bevacizumab-IRDye800CW enabled detection of fluorescence signals intraoperatively. Secondary objectives were correlation of fluorescence with histopathology by back-table imaging of the fresh surgical specimen and semi-quantitative ex-vivo analyses of formalin-fixed paraffin embedded (FFPE) tissue on all peritoneal lesions. Additionally, VEGF-α staining and fluorescence microscopy was done. This study is registered with the Netherlands Trial Registry, number NTR4632. Findings: Between July 3, 2014, and March 2, 2015, seven patients were enrolled in the study. One patient developed an abdominal sepsis 5 days postoperatively and another died from an asystole 4 days postoperatively, most probably due to a cardiovascular thromboembolic event. However, both serious adverse events were attributed to the surgical cytoreductive surgery and HIPEC procedure. No serious adverse events related to bevacizumab-IRDye800CW occurred in any of the patients. Intraoperatively, fluorescence was seen in all patients. In two patients, additional tumour tissue was detected by molecular fluorescence-guided surgery that was initially missed by the surgeons. During back-table imaging of fresh surgical specimens, a total of 80 areas were imaged, marked, and analysed. All of the 29 non-fluorescent areas were found to contain only benign tissue, whereas tumour tissue was detected in 27 of 51 fluorescent areas (53%). Ex-vivo semi-quantification of 79 FFPE peritoneal lesions showed a tumour-to-normal ratio of 6·92 (SD 2·47). Interpretation: Molecular fluorescence-guided surgery using the near-infrared fluorescent tracer bevacizumab-IRDye800CW is safe and feasible. This technique might be of added value for the treatment of patients with colorectal peritoneal metastases through improved patient selection and optimisation of cytoreductive surgery. A subsequent multicentre phase 2 trial is needed to make a definitive assessment of the diagnostic accuracy and the effect on clinical decision making of molecular fluorescence-guided surgery. Funding: FP-7 Framework Programme BetaCure and SurgVision BV.